The Effect of Variation in Electrode Type and Area on Electrical Productivity of MFC With Sago Stem Substrate - Ramadhan, Muhammad Nizar; Hamdani, Rizal (Universitas Muhammadiyah Jakarta, 2024)
Microbial Fuel Cells (MFC) offer a promising solution for developing efficient and environmentally friendly alternative energy sources. MFCs convert chemical energy into electrical energy through anaerobic reactors equipped with anode and cathode electrodes containing substrates and microbes. This study investigates the effect of electrode type and area on the production of current, voltage, and power density using sago stem substrates in an MFC system enhanced with Lactobacillus plantarum. These bacteria play a critical role in facilitating electrolysis, thereby increasing electrical energy output. A dual-chamber MFC design was employed, testing electrode materials (copper, aluminum, nickel, and graphite carbon) and areas (30 cm², 40 cm², and 60 cm²). Measurements of current, voltage, and power density were taken over 36 hours. Results indicate that electrode area significantly influences voltage and current, while electrode type determines power density. The highest average power density, 432.953 mW/m², was achieved using nickel electrodes with a 30 cm² surface area. These findings underscore the importance of optimizing electrode properties to enhance the performance of MFCs.